2012
DOI: 10.1007/s12079-012-0158-2
|View full text |Cite
|
Sign up to set email alerts
|

CCN5/WISP-2: A micromanager of breast cancer progression

Abstract: The gain of plasticity by a subset of cancer cells is a unique but common sequence of cancer progression from epithelial phenotype to mesenchymal phenotype (EMT) that is followed by migration, invasion and metastasis to a distant organ, and drug resistance. Despite multiple studies, it is still unclear how cancer cells regulate plasticity. Recent studies from our laboratory and others' proposed that CCN5/WISP-2, which is found intracellularly (in the nucleus and cytoplasm) and extracellularly, plays a negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 102 publications
4
63
0
Order By: Relevance
“…Furthermore, recent data indicate that WISP2 can block expression of miR-10b [20], a non-coding RNA known to play a role in invasion and metastasis [21]. Taken together, these findings suggest that loss of WISP2 is associated with breast cancer progression [22].…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, recent data indicate that WISP2 can block expression of miR-10b [20], a non-coding RNA known to play a role in invasion and metastasis [21]. Taken together, these findings suggest that loss of WISP2 is associated with breast cancer progression [22].…”
Section: Introductionmentioning
confidence: 86%
“…Furthermore, in vivo studies have shown that CCN5 expression is mainly detected in preneoplastic disorders, such as non-invasive DCIS (ductal carcinoma in situ) and atypical ductal hyperplasia, whereas expression levels were either minimal or undetectable in invasive cancer cells [16,18]. These studies indicate that loss of CCN5 activity may promote breast cancer progression [19].…”
Section: Introductionmentioning
confidence: 91%
“…Tip30 mutant derived from HCC patient was able to upregulate N‐cadherin and downregulate E‐cadherin . Insulin‐like growth factor 1 and WNT1‐ inducible signaling pathway protein 2, two important regulators of EMT, were found increased in Tip30‐ null MECs . TIP30 was also found to be involved in Sorafenib‐induced EMT in HCC cells .…”
Section: Discussionmentioning
confidence: 94%
“…14 Insulin-like growth factor 1 and WNT1-inducible signaling pathway protein 2, two important regulators of EMT, were found increased in Tip30-null MECs. [45][46][47] TIP30 was also found to be involved in Sorafenibinduced EMT in HCC cells. 48 Our in vitro data confirm that decreased TIP30 is able to induce EMT in PDAC cells.…”
Section: Discussionmentioning
confidence: 96%